Effect of shrinkwrapping and paraffin waxing on the shelf life of pineapples stored at various temperatures. - Mohamed, Suhaila; Mohd. Khir, Safiah (1990)
Stored pineapples exhibit weight loss, over ripening, fungal attack and sometimes internal browning disorder during storage. The effect of paraffin coating and shrinkwrapping on Mauritius pineapples stored at 10⁰C, 15⁰C, 20⁰C and ambient were studied. Weight loss and texture loss (firmness) was least in shrinkwrapped pineapples, followed by paraffin coated ones. This was attributed to the high relative humidity, high CO2 and low O2 level inside the packaging. Paraffin coating was effective in inhibiting internal browning disorder in pineapples stored at 10-20⁰C to between 7-11 weeks respectively. Paraffin coating also reduced the acidity of the pineapples, helped retain the total soluble solids content and ascorbic acid content of pineapples stored at the lower temperatures. This was thought to be due the reduction of oxygen level in the tissue. Combination of paraffin waxing and shrinkwrapping was found to be effective in maintaining all the parameters studied except for texture.